Theory and practice of dialectical behavioral therapy - Andrushko Yaryna Stepanivna (Insight: the psychological dimensions of society, 2022)
Dialectical behavioral therapy (DBT) is an empiricallyproven method of helping patients with borderlinedisorders and suicidal tendencies. Dialectical-behavioraltherapy is aimed at orienting a person in personalchanges, increasing behavioral standards, workingwith acceptance. At the same time, the therapist playsthe role of a guide who helps to calm down, encourageand help the patient to survive this experience.The purpose of the study is the theoretical-practicalanalysis of dialectical-behavioral therapy and classicaltechniques of this psychotherapeutic direction.Research methods: theoretical, in particular analysisand synthesis, generalization, systematizationand explanation. The results. The clinical utility associatedwith the use of DBT in an inpatient setting abroadhas been substantiated. The specificity of treatmentis effective and contributes to the reduction of symptomsof borderline personality disorder and improvementof global functioning when standard practicesand principles are incorporated with reliability intodefined treatment models. It is noted that research isnecessary for the standardization of DBT in the hospital and the results of measurements in Ukrainian realities,which will help to determine the critical mechanismsof symptoms and behavior, change and evaluatethe effectiveness of further outpatient treatment. DBTis the treatment model with the most published scientificarticles showing effectiveness. Some techniquesof the dialectical-behavioral direction are analyzed.Conclusions. In general, each strategy used in DBTrequires a dialectical approach that combines changeand acceptance. Separated techniques of the dialectic-behavioral direction allow the individual to becomemore persistent and effective in interpersonal communication,contribute to the formation of the ability toexpress one’s needs and at the same time the ability tosay “no”, while the individual is focused on the positiveand constructive. The development of tolerance skillswhen overcoming stress in dialectic-behavioral therapyis not a little important.